A Decision-Support Framework for Composite Curved Beam Design under Moving Loads: Dynamic Modelling and Multi-Criteria Evaluation - Nihayat Hussein Ameen (Decision Making: Applications in Management and Engineering, 2025)
Behavior of curved beams subjected to moving loads has specific application in the structural design of bridges, railways, as well as machining frames. With the growth in applications of the composite material in structural members, in the form of beams, plates, as well as in columns, the stringent analysis of their transient loading behavior has been made inevitable. This paper investigates the dynamics of a moderately deep, orthotropic curved composite beam subjected to moving mass loads. Analysis is based on the first-order shear deformation theory in combination with Hamilton’s principle, for the identification of the governing partial differential equations in the spatial as well as time domains. These equations are then reduced to ordinary differential equations in the spatial domain using Navier’s method, while the temporal aspect is resolved using Newmark’s numerical integration scheme. The accuracy of the model's natural frequency predictions is validated through comparison with both straight and curved composite beam configurations, as well as with cases involving moving mass loads, demonstrating strong agreement with previously published results. In practical engineering scenarios, particularly in high-speed railway systems and aerospace structures, selecting the optimal configuration of curved composite beams necessitates careful consideration of factors such as stiffness, weight, manufacturability, and resilience to dynamic loading. The study reveals that increasing the mass and length of the beam leads to a notable amplification in its dynamic response. Additionally, the stacking sequence and orientation of the composite layers play a decisive role in influencing vibrational behaviour. Nonetheless, the configuration of the layers profoundly affects the dynamic responding related to the beam curved counting on a moving mass, with the amplitude of structural oscillations being maximized for layers and minimized for layers. To support optimal design strategies, a Multi-Criteria Decision-Making (MCDM) framework is introduced, enabling a structured evaluation of trade-offs among structural stiffness, mass, cost, and vibration performance. The findings underscore the necessity of such a decision-making tool in selecting optimal beam configurations under realistic dynamic loading conditions, considering variables such as load velocity, curvature, and anisotropic material behaviour. This research offers practical guidance for engineers in choosing suitable laminate architectures and materials to reduce vibration and enhance durability in transportation and civil engineering infrastructure. The study contributes to informed decision-making in high-speed rail and aerospace applications, where control of dynamic performance is of critical importance.